Teaching And Learning Process Of Speaking At The Fourth Semester Of English Department Of UMS In 2016/2017 Academic Year - Fithri H, Yuliana; , Mauly Halwat Hikmat,Ph.D (2016)
Yuliana Fithri H. A320120012. TEACHING AND LEARNING PROCESS OF SPEAKING AT THE FOURTH SEMESTER OF ENGLISH DEPARTMENT OF UMS IN 2016/2017 ACADEMIC YEAR. Research Paper. School of Teacher Training and Education. Muhammadiyah University of Surakarta. 2016 The objectives of this study are to describe the implementation of teaching learning process of speaking at the fourth semester of English Department of UMS in 2016/2017 academic year and the problems faced by the students and lecturer in teaching learning process of speaking at the fourth semester of English Department of UMS in 2016/2017 academic year. The research is qualitative research. The subject of the study is the English lecturer and the students of the fourth semester of English Department of UMS 2016/2017 academic year. The object of the study is teaching learning process of speaking at the fourth semester of English Department of UMS in 2016/2017 academic year. The method of collecting data are observation, interview, document analysis. The technique of analyzing data are data reduction, data display, and conclusion and verification. The results of the study shows that the materials of teaching learning process of speaking at the fourth semester of English Department of UMS in 2016/2017 academic year were 'opening speech' and 'academic presentation'. There are three steps in teaching those materials in class, which consists of explaining, rehearsing, and reinforcing. The problems faced by lecturer in teaching learning process of speaking are situation is too crowded, the lecturer is exhausted because too much power and strength are wasted, and students often present the materials by reading the text. The problems faced by the students in learning process of speaking are limited class time, lack of vocabulary, and student's anxiety. Keywords: descriptive, speaking teaching learning, opening speech, academic presentation.